Lama Penyimpanan dan Perendaman Benih Padi Ketan Merah (Oryza Sativa L. Var, Glutinosa) Didalam Air Kelapa dan Air Mineral terhadap Perkecambahan - Candra Kurniawan; Abdul Karim Kilkoda; Martini K. Leisilolo (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2025)
Red glutinous rice is one of the rice varieties that has advantages over white rice because it contains high amounts of phenolic compounds. Seeds are an important factor that determines the success of plant growth, but storage time can affect its quality. One technique to increase the germination ability of seeds after storage is by soaking them using coconut water or mineral water. Coconut water functions as a natural growth regulator that is able to stimulate the germination process. This study aims to determine the effect of storage time and type of soaking of red glutinous rice seeds (Oryza sativa L. var. glutinosa) in old coconut water and mineral water. The research was carried out at the Physiology Laboratory of Pattimura University Ambon from December 2024 to February 2025 using a two-factor Complete Random Design (RAL), namely storage time (0, 2, 4, 6, and 8 weeks) and the type of immersion (mineral water and old coconut water). The results showed that seeds without storage produced the highest germination power of 99%. Soaking seeds with mineral water at six weeks of storage gave the best results with a growth rate of 14.25%, growth evenness of 67.20%, and a vigor index of 11.02. The interaction between storage time and soaking type has a very real effect on growth speed, real on the vigor index, but no real effect on germination, speed, and germination of seeds.